ENHANCING RICE AND WHEAT PRODUCTIVITY THROUGH RHIZOSPHERE ACTIVE HIGH YIELD TECHNOLOGY MICROBIAL PRODUCT - D. K. SINGH; P. C. PANDEY; SHILPI GUPTA; DIPTI BISARYA (The Bioscan, 2015)
Field experiments were conducted during both kharif and rabi seasons (2010-11 to 2012-13) to study the root parameters,yield, attributes,yields and nutrient use efficiency (partial factor productivity) under rice (Oryza sativa L) wheat (Triticum aestivum L.) cropping system. The experiment was laid out in randomized block design with seven treatments in three replications. The results indicated that recommended NPK (N120 P60 K40) with higher dose of HYT A+B+C increased the growth, yields and yield parameters. Rice grain yield in N120P60 K40 with higher dose of HYT A+B+C was recorded significantly higher of the order of 4474, 5556 and 6462kg/ha during all three years 2010, 2011 and 2012, respectively which was 10.9, 8.5 and 13.5 % higher during the respective years over the recommended NPK dose of fertilizer (N120P60K40). Similarly, wheat grain yield in N120P60K40 with higher dose of HYT A+B+C was significantly higher emanating 25.8, 29.9 and 25.3% higher yield in 2010-11, 2011-12 and 2012-13, respectively over recommended NPK treatment. It can be summarized that application of recommended NPK with higher dose of HYT A+B+C exhibited best results in both rice and wheat in terms of root volumes, yields and yield parameters and partial factor productivity over three consecutive years of experimentation.